Efficacy and safety of the pulsed electromagnetic field in osteoarthritis: a meta-analysis - Ziying Wu; Xiang Ding; Guanghua Lei; Chao Zeng; Jie Wei; Jiatian Li; Hui Li; Tuo Yang; Yang Cui; Yilin Xiong; Yilun Wang; Dongxing Xie (BMJ Open)
Objective To investigate the efficacy and safety of the pulsed electromagnetic field (PEMF) therapy in treating osteoarthritis (OA).Design Meta-analysis.Data sources PubMed, Embase, the Cochrane Library and Web of Science were searched through 13 October 2017.Eligibility criteria for selecting studies Randomised controlled trials compared the efficacy of PEMF therapy with sham control in patients with OA.Data extraction and synthesis Pain, function, adverse effects and characteristics of participants were extracted. RevMan V.5.2 was used to perform statistical analyses.Results Twelve trials were included, among which ten trials involved knee OA, two involved cervical OA and one involved hand OA. The PEMF group showed more significant pain alleviation than the sham group in knee OA (standardised mean differences (SMD)=−0.54, 95% CI −1.04 to –0.04, p=0.03) and hand OA (SMD=−2.85, 95% CI −3.65 to –2.04, p<0.00001), but not in cervical OA. Similarly, comparing with the sham–control treatment, significant function improvement was observed in the PEMF group in both knee and hand OA patients (SMD=−0.34, 95% CI −0.53 to –0.14, p=0.0006, and SMD=−1.49, 95% CI −2.12 to –0.86, p<0.00001, respectively), but not in patients with cervical OA. Sensitivity analyses suggested that the exposure duration <=30 min per session exhibited better effects compared with the exposure duration >30 min per session. Three trials reported adverse events, and the combined results showed that there was no significant difference between PEMF and the sham group.Conclusions PEMF could alleviate pain and improve physical function for patients with knee and hand OA, but not for patients with cervical OA. Meanwhile, a short PEMF treatment duration (within 30 min) may achieve more favourable efficacy. However, given the limited number of study available in hand and cervical OA, the implication of this conclusion should be cautious for hand and cervical OA.